Proposta de atividades para auxiliar o ensino de Matemática utilizando conceitos de Pensamento Computacional e robô programável - Padua, Yuri Souza (Universidade Federal de São Carlos, 2020)
The country's education is central topic of many discussions due to the complexity associated with its multiple variables.The Programme for International Student Assessment - PISA - is one of the most relevant indicators, in which Brazil has not achieved good ranking especially when compared to South America countries. Among the weaknesses of the Brazilian educational structure, there is the need to insert more technology, such as robotics, programming and/or Computational Thinking as regular disciplinary content. However, the recently enacted Common National Curricular Base (BNCC in portuguese) - does not recognize these subjects as regular and / or essential in basic education, except for some aspects of Computational Thinking - CT. On the other hand, several countries in which technology integrates the curriculum, are among the best ranked in the same exams and, although these subjects are not predominantly responsible for superior performance, it is a motivating approach due to its adherence of these contents to demands of Science and everyday life. Considering the context presented above, this master's thesis aims to collaborate with suggestions for incorporating the CT and Educational Robotics in regular subjects for elementary school 1, taking into account several authors recommendations of interdisciplinarity between the CT and the regular subjects of basic education in the real environment, devoting more attention to the participants and the methodological approach rather than the technologies used. Therefore, the objective of this investigation is to propose, teach and evaluate activities-classes that contribute to teaching of Mathematics and Computational Thinking in regular classes and using a programmable robot. The methodology used in the research was a qualitative and quantitative multiple-case study, being the first pilot-case with 3 classes from a public school with approximately 36h of classes, in which were collected data of the participants, LOGs of the algorithms and their opinions about classes using emoti-SAM and with approximately 80\% positive considerations. Similarly, in the second case study, 90h of classes were given to 91 children, totaling approximately 1,100 records collected with emoti-SAM, 23h of interviews, LOGs of the algorithms, pre/post-test and also the opinion of the participating teachers. Finally, the 18 Lesson Plans proposed, already taught in schools and evaluated in this master's degree are made available in this thesis. The main goal of this research is to contribute to discussions on unusual ways of approaching regular disciplines under the context of computational thinking and educational robotics.
Proposed activities to assist the teaching of Mathematics using concepts of Computational Thinking and programmable robot
Propuestas de actividades para ayudar a la enseñanza de las Matemáticas utilizando conceptos de Pensamiento Computacional y robot programable
Keywords: Pensamento Computacional; Robótica Educacional; Matemática; Base Nacional Comum Curricular; Ensino Fundamental; Plano de aula; Plataforma Zerobot; Computational Thinking; Educational Robotics; Mathematics; Common National Curricular Base; Elementary School; Class plan; Zerobot platform; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO